Poscovid urban reconfiguration: spatial behavior of commerceand services in the Guadalajara Metropolitan area - Sevilla Villalobos, Salvador (2025)
After COVID-19, cities have faced changes in their dynamics due to the global readjustment of value chains. Using coefficients and spatial models, particularly an adaptation of the Gini index, this paper explores the spatial behaviors and business sizes in the Guadalajara Metropolitan Area in two strategic sectors during the first two years following the pandemic: the business support sector and retail trade. The results show that these sectors exhibit inverse behavior. Contrary to the discourse on urban outsourcing, retail trade has increased its presence in the study area, while the business support sector has shown less territorial expansion. It is concluded that this situation may reflectthe processes of urban outsourcing in Latin American cities, where dependence on theGlobal North influences the perception of the service sector as physically expendable due to its ability to operate through digital platforms and the institutionalization of digitalization as a primary necessity. In contrast, retail trade has diversified and established itself as an outsourced element with a presence in multiple territories.